980-nm all-fiber mode-locked Yb-doped phosphate fiber oscillator based on semiconductor saturable absorber mirror and its amplifier - 李平雪 姚毅飞 池俊杰 胡浩伟 张光举 梁博兴 张孟孟 马春媚 苏宁 (Chinese physics B, 2016)
A 980-nm semiconductor saturable absorber mirror（SESAM） mode-locked Yb-doped phosphate fiber laser is demonstrated by using an all-fiber linear cavity configuration. Two different kinds of cavity lengths are introduced into the oscillator to obtain a robust and stable mode-locked seed source. When the cavity length is chosen to be 6 m, the oscillator generates an average output power of 3.5 m W and a pulse width of 76.27 ps with a repetition rate of 17.08 MHz. As the cavity length is optimized to short, 4.4-m W maximum output power and 61.15-ps pulse width are produced at a repetition rate of 20.96 MHz. The output spectrum is centered at 980 nm with a narrow spectral bandwidth of 0.13 nm. In the experiment, no undesired amplified spontaneous emission（ASE） nor harmful oscillation around 1030 nm is observed. Moreover,through a two-stage all-fiber-integrated amplifier, an output power of 740 m W is generated with a pulse width of 200 ps.